2004
DOI: 10.1115/1.1637925
|View full text |Cite
|
Sign up to set email alerts
|

Double-Species Slurry Flow in a Horizontal Pipeline

Abstract: Slurry transport experiments were performed with five double-species slurries composed of glass beads and water. The double-species glass beads were various combinations of beads having two widely different densities and three narrow particle size distributions. Pressure gradients for double-species slurries were compared to those for individual components at the same solids volume concentrations. Effect of mean particle diameter on pressure gradient of double-species slurry in the pipe was studied. Experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…It is more rational to consider the solid phase as two components according to two peaks of particle size distribution and the moment exchange between different solid phases needs to be included. At present, only few studies [16,17] have reported experimental results on double-solid-phases slurry flow. Our numerical results show more important flow characteristics than these reported.…”
Section: Introductionmentioning
confidence: 96%
“…It is more rational to consider the solid phase as two components according to two peaks of particle size distribution and the moment exchange between different solid phases needs to be included. At present, only few studies [16,17] have reported experimental results on double-solid-phases slurry flow. Our numerical results show more important flow characteristics than these reported.…”
Section: Introductionmentioning
confidence: 96%
“…The theoretical result is based on, and confirmed by, extensive testing of large diameter commercial pipelines transporting coal-water slurries (Skudarnov et al, 2004). This method provides a means of interpolation between flow pattern extremes of homogeneous flow and heterogeneous flow to estimate the pressure gradient for mixed-size slurries.…”
Section: Pressure Drop In Multi-particle Slurriesmentioning
confidence: 70%
“…Studies to determine the effect of two different particle characteristics on the pressure drop measurements were performed by Skudarnov et al (2004) using silica and zircon sands transported in water. The sands have different densities but the same particle size range.…”
Section: Pressure Drop In Multi-particle Slurriesmentioning
confidence: 99%
“…Factors affecting the pressure gradient have been examined by several researchers such as Newitt et al (1955), Maruyama et al (1979), Lin (1982), Doron and Barnea Charles, 1970). (1993,1996), Doron et al (1997), Gillies et al (1999), Skudarnov et al (2004), Greenspan and Nigam (2001), Kaushal and Tomita (2002), Kaushal et al (2005), and Matousek (2002).…”
Section: Hydrotransport Flow Regime Characterization Methodsmentioning
confidence: 97%
“…Suspended particle flow results in an increased pressure gradient with velocity (Newitt et al, 1955). Skudarnov et al (2004) determined that the critical velocity for the formation of moving and stationary beds are directly related to increased solids concentrations, as well as to increasing specific gravity of the transported material. Maruyama et al (1979) studied the hydrotransport of glass beads in horizontal pipes using visual observations and pressure measurements.…”
Section: Hydrotransport Flow Regime Characterization Methodsmentioning
confidence: 99%